Pitchers : twenty-seven of baseball's greatest - Sullivan, George, 1927- (New York : Atheneum : Maxwell Macmillan International, 1994)
Text and accompanying photographs profile twenty-seven of the best pitchers in the history of baseball, including Nolan Ryan, Tom Seaver, Whitey Ford, Dizzy Dean, and Cy Young.
Includes index.
Wilson's Children.
Elem. School Library Collection.
Notable/Best Books (A.L.A.).
5.9
5-8
Keywords: Pitchers (Baseball) -- United States -- Biography -- Juvenile literature; Pitchers (Baseball); Baseball players; Pitchers (Baseball); Baseball players -- Biography; Pitchers (Baseball); Baseball players